Pregnant and breastfeeding women’s prospective acceptability of two biomedical HIV prevention approaches in Sub Saharan Africa: A multisite qualitative analysis using the Theoretical Framework of Acceptability - Mandeep Sekhon (Public Library of Science (PLoS), 2021)
HIV infection during pregnancy and breastfeeding has implications for maternal health. Between May- November 2018, we explored prospective acceptability of two novel HIV Pre-exposure Prophylaxis (PrEP) products, oral pills and vaginal rings, through focus group discussions with 65 pregnant and breastfeeding women in Malawi, South Africa, Uganda, Zimbabwe. Qualitative analysis was completed, guided by the Theoretical Framework of Acceptability (TFA). First, a deductive thematic analysis was applied to relevant coded data, into the seven TFA constructs (Affective Attitude; Burden; Ethicality, Intervention Coherence; Opportunity Costs; Perceived Effectiveness; Self-efficacy). Next, an iterative analysis was completed to generate themes within each of the TFA constructs. Women’s positive attitudes towards daily oral PrEP highlighted the familiarity of taking pills, understanding the purpose of taking pills, and the perception that it is an effective method to protect mothers and babies from HIV during pregnancy and breastfeeding. Women emphasized the ease of using the ring given its monthly duration that lowers burden on the user, its discreetness and invisibility once in place. The TFA analysis highlighted how acceptability of both methods could be enhanced by focusing on perceptions of the end users (i.e. the women) and not just the products themselves. This approach provided insights into how to refine the intervention materials and plans for implementation.